The Protective Role of Date Palm Pollen (Phoenix dactylifera L.) on Liver Function in Adult Male Rats Treated with Carbon Tetrachloride - Araak, Jawad Kadhim (The Iraqi Journal of Veterinary Medicine, 2012)
The present study was carried out to investigate the protective role of date palm pollenaqueous suspension against the toxic effects of carbon tetrachlorideon liver function in adultmale rats by studying the following parameters,estimation of ALP, AST, ALT enzymesactivity, totalserum bilirubin, and histological study of liver.Forty adult male rats aged 12-14weeks and weighed 275-325 gm were randomly divided into four equal groups(10 rats/group)and were treated for 42 days as follows : rats of the first group were received 1 ml tap waterorally once a day and olive oil 0.5 ml /kg B.W. intraperitonelly twice a week whichconsidered as group C, rats of the second group were received date palm pollen suspensionorally (150 mg/kg B.W) once a day and olive oil 0.5 ml /kg B.W. intraperitonelly twice aweek( group T1),rats of the third group were treated intraperitonelly with 500mg / kg B.W. ofCCL4 mixed with equal volume of olive oil twice a week (group T2) ,while rats of the fourthgroup were received date palm pollen suspension (150 mg/kgB.W) once a day orally andtreated intraperitonelly with 500 mg / kg B.W. of CCL4 mixing with equal volume of oliveoil twice a week (group T3). The blood samples were collected at (zero, 14, 28, 42) days forbiochemical parameters. After that, six rats from each group were sacrificed, and thensamples of liver were taken for histological study. The results revealed no significantdifferences (P > 0.05)in Liver Enzymes activity (ALT , AST , ALP ) as well asserumBilirubin (TSB) inT1 group treated with date palm pollen comporting with control groupwhile a significant elevation(P ≤ 0.05) in liver Enzymes (ALT , AST , ALP ) activity and totalserum bilirubin (TSB) in group T2 which exposed to carbon tetrachloride.the protective roleof date palm pollen against carbon tetrachloride was recorded in group T3 which manifestedby significant differences (P>0.05) in liver enzymes activity (ALT , AST , ALP ) and serumbilirubin (TSB) as compared to the control.The histological study of liverof date palm pollentreated rats (group T1) indicated proliferation of kupffer cells and no nuclear lesion, whilegroup T2 showed severe vacuolation in the hepatocytes, while group T3 showed moderatevacuolation in hepatocytes.From the result obtained ,it was concluded that it seems likely thatdosage of rats with (150 mg/kg B.W) of date palm pollen for 42 days of treatment causedimprovement and enhancement of liver function against carbon tetrachloride harmful effects.